1996
DOI: 10.1097/00004694-199603000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Dynamic Screw Fixation of the Asymptomatic Hip in Slipped Capital Femoral Epiphysis

Abstract: Prophylactic dynamic screw fixation (DSF) of clinically and radiographically unaffected hips of 34 patients with a contralateral slipped capital femoral epiphysis and no evidence of an endocrinopathy or systemic disorder was performed using a single cannulated screw. Follow-up ranged from 2 to 12 years (average, 5.4 years). There was no case of perioperative complication and no avascular necrosis or chondrolysis occurred. No preslip or slip became apparent. In all 34 hips, no tendency toward premature closure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 11 publications
2
18
0
1
Order By: Relevance
“…One patient (1.5%) developed a superficial wound infection, but there were no cases of AVN, chondrolysis, or pain requiring implant removal. Finally, Kumm et al [16] described 34 patients with SCFE treated with prophylactic dynamic screw fixation of the unaffected hip. The authors reported no complications in their series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One patient (1.5%) developed a superficial wound infection, but there were no cases of AVN, chondrolysis, or pain requiring implant removal. Finally, Kumm et al [16] described 34 patients with SCFE treated with prophylactic dynamic screw fixation of the unaffected hip. The authors reported no complications in their series.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of a subsequent slip on the side that is initially normal is reportedly between 14% and 40% [12,14,15,18,22,26]. Many authors support routine prophylactic pinning of the contralateral, normal side to prevent the morbidity associated with a subsequent SCFE, which can include pain and loss of motion, as well as the development of femoroacetabular impingement, chondrolysis, and avascular necrosis (AVN) [8,11,12,16,20,22,23,26]. Others argue routine prophylactic pinning for all patients with a unilateral SCFE will result in an unnecessary surgery for most patients [6,7,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Hagglund (1 996) recommended that, at centers with a low complication rate of pinning, prophylactic pinning should be performed in all children. Kumm et al (1996) found no perioperative complications after prophylactic dynamic screw fixation of the asymptomatic hip in 34 patients at an average follow-up of 5 years. No avascular necrosis or chondrolysis occurred.…”
Section: Axial View Of the Right Hipmentioning
confidence: 80%
“…The incidence differs ac-cording to the radiographic assessment (Hagglund et al 1988, Canaie 1989, Engelhardt 1994, Hagglund 1996, Jerre et al 1996. However, there is no agreement about prophylactic stabilization of the contralateral hip joint (Imhauser 1987, Crawford 1988, Canale 1989, Engelhardt 1994, Kumm et al 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Normal kalçada AP grafide femur boynu superiorundan teğet çizilen çizgi (Klein çizgisi) femur başı epifizinin lateralinin bir kısmını keser (Şekil 3). [27] Femur başı posteriora deplase olursa Klein çizgisi femur başı epifizinin çok az bir kısmını keser, tam kaymalarda ise epifizi kesmeyebilir (Trethowan bulgusu).…”
Section: Radyoloji̇k Bulgular Röntgenogramunclassified